Assessment of physical health characteristics in selected Selangor rivers in Malaysia - Hashim, Rohasliney; Hittage, Nadeesha Dilani; Jamil, Nor Rohaizah; Ash'aari, Zulfa Hanan; Kutty, Ahmad Abas (Faculty of Science, Universiti Putra Malaysia, 2024)
This research aims to evaluate the physical habitat quality of the Rawang sub-basin of the Selangor River. Seven river sampling sites were selected, including Guntong (SR1), Guntong’s tributaries (SR2/reference), Kuang (SR3 and SR7), Gong (SR4), Buaya (SR5), and Serendah (SR6) using random sampling techniques based on accessibility and proximity to freshwater fish farms. The habitat assessment was performed during the rainy and dry seasons in August 2019 and December 2019, respectively. Results indicated that the Guntong River tributary (reference site) recorded the highest Qualitative Habitat Evaluation Index (QHEI) (14.99) compared to the other locations under the suboptimal condition (11 – 15.9). The average habitat score of other sampling sites under the suboptimal condition, namely Guntong (SR1), Kuang (SR3), Buaya (SR5), and Serendah (SR6) Rivers, were recorded as 13.16, 11.30, 12.58, and 14.05, respectively. Meanwhile, the Kuang River (SR7) score was 10.65 under the marginal condition (6 – 10.9). This study’s lowest average habitat score was the Gong River (SR4) under marginal conditions (10.61). To conclude, this study showed that the QHEI is a helpful tool in identifying the potentially unsustainable fish farming impacted river sites to evaluate the river’s physical health.